MELO CARRASCO, Diego y MANZANO RODRÍGUEZ, Miguel Ángel (coords.). Al-Andalus y el Magreb: miradas trasatlánticas. Presentación Ángel G. Gordo Molina. Gijón: Trea, 2019, 197 págs. ISBN: 978-84-17767-25-9. - Elena MOLINA LÓPEZ (Al-Andalus Magreb, 2023)
Reseña de la obra mencionada